Comparative Study of AODV andDSR Routing Protocols forGateway Placement Optimization - Al-Bayati, Jamal Muafaq Hameed (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper considers mobile ad-hoc network (MANET) in which mobile nodes can reach the Internet via stationary gateway node. The gateway works as bridge between MANET and the Internet. Several studies show that location of the gateway inside network topology has a significant effect on overall network performance. Two different scenarios, with varying number of nodes and two gateway locations, have been considered under the assumption that all mobile nodes are connected to Internet through the same gateway. Simulation has been done using NS-2 software, producing a computer model of AODV and DSR routing protocols. Comparison of these routing protocols is performed in terms of Average (end-to-end) delay, Throughput, Normalized routing load and Packet delivery ratio metrics. Simulation results suggest that AODV routing protocol has better performance in both scenarios. In addition, the results suggest that location of gateway at the center gives better results compared to gateway positioned at the edge.